Unveiling effective CSCL constructs for STEM education in Malaysia and Indonesia - Mohamed Zahir, Nur Zahira; Hashim, Suhaizal; Abdul ahman, Khairul Anuar; Zulkifli, Nurul Nadwa; Riyadi, Slamet; Siswantoro, Joko (Semarak Ilmu Publishing, 2025)
The acquisition of knowledge and skills in the fields of Science, Technology, Engineering, and Mathematics (STEM) plays a crucial role in fostering the development of future innovators. These subjects are critical for creating future thinkers. Additionally, it is important to note that there are a lot of job openings in the STEM fields, and this trend is expected to keep growing. However, students don’t seem to be as motivated to study in STEM fields or work in STEM fields. One teaching method that is becoming more popular is computer-supported collaborative learning (CSCL). This is because it can have a big effect on how people learn, especially in STEM subjects. It is very important to set up a CSCL learning environment for STEM schooling right away. However, that there isn’t a good framework and there aren’t many widely used design methods in this area. Without a question, there is a strong need to learn more about design methodologies in the areas of collaborative and technology-enhanced learning to come up with simple methods for CSCL. Because of this, the goal of this study is to investigate the conceptual parts of CSCL methods in STEM education. This will be used to make CSCL educational methods that are good especially for STEM education. STEM academics in Malaysia and Indonesia were surveyed using questionnaires to find the most important parts of CSCL strategies in STEM education, and the results were analysed using the Fuzzy Delphi Method. The results give us a list of CSCL settings used in schools, which can be used as a guide for creating and using CSCL strategies in STEM education.